Optimizing Waqf Management For Social Impact - Arizqiya Nurfattah; Royyan Bachtiar (Islamic Business and Management Journal, 2023)
Waqf is a distinctive instrument in the Islamic financial system that aims to provide social and economic benefits to society. In Indonesia, waqf has great potential to improve people's welfare, support social and economic development, and advance various sectors in the country, such as issues of access to education and health, among others. This is inseparable from the optimal management of waqf management which is the life of waqf sustainability. This paper reviews good waqf management supported by all aspects including digital aspects, and discusses the challenges faced by the development of digital technologies such as websites, blockchains, and so on in facilitating the management and development of waqf in Indonesia so that it can follow the pattern of steps in the digital era. The results of the study explain that digital innovations such as websites, blockchain, and others are very helpful in carrying out clearer and more accountable waqf management. In other words, the welfare of the state and society is supported by social activities derived from waqf assets, productive investment, and Sharia compliance. Optimal waqf management involves all aspects consisting of sharia compliance, regulations, and the use of adequate technology that has an impact on social activities, education, and even productive investment of waqf assets.